1996
DOI: 10.1002/j.1460-2075.1996.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of growth polarity and mislocalization of septa in a Neurospora mutant altered in the regulatory subunit of cAMP-dependent protein kinase.

Abstract: In filamentous fungi, growth polarity (i.e. hyphal extension) and formation of septa require polarized deposition of new cell wall material. To explore this process, we analyzed a conditional Neurospora crassa mutant, mcb, which showed a complete loss of growth polarity when incubated at the restrictive temperature. Cloning and DNA sequence analysis of the mcb gene revealed that it encodes a regulatory subunit of cAMP‐dependent protein kinase (PKA). Unexpectedly, the mcb mutant still formed septa when grown at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 65 publications
9
100
0
Order By: Relevance
“…The mcb (microcyclic conidiation) mutant of N. crassa, which is known to be a mutant of the PKA regulatory subunit gene, exhibits loss of growth polarity at restrictive temperatures, possibly due to altered organization of actin patches at the cell cortex (Bruno et al 1996). The morphology of the double mutant pkac-1 mcb resembles that of the pkac-1 mutants (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The mcb (microcyclic conidiation) mutant of N. crassa, which is known to be a mutant of the PKA regulatory subunit gene, exhibits loss of growth polarity at restrictive temperatures, possibly due to altered organization of actin patches at the cell cortex (Bruno et al 1996). The morphology of the double mutant pkac-1 mcb resembles that of the pkac-1 mutants (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Suppression of the abnormal growth polarity of the mcb strain by the pkac-1 gene mutation indicates that PKAC-1 activity is essential for the mcb phenotype. The mcb mutant has increased expression of two overlapping transcriptional units, and loss of polarity is suppressed by cr-1 (Bruno et al 1996), suggesting that the mcb mutant is not a null mutant of the regulatory subunit gene. Further studies will be necessary to clarify the function of the regulatory subunit in cell polarity in the mcb mutant of N. crassa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As environmental suppression of both kinases was correlated with reduced PKA activity levels, we analyzed PKA activity in the Dmak-2 strain and found several lines of evidence for reduced PKA activity. mcb is a temperaturesensitive mutant defective in the regulatory subunit of PKA, which displays elevated PKA activity levels at restrictive temperature, resulting in apolar growth and irregular chains of spherical cells (Bruno et al 1996a;Seiler et al 2006;Ziv et al 2008). Genetic analysis of a Dmak-2;mcb(14-4) double mutant demonstrated that Dmak-2;mcb(14-4) grew slower than the parental strains at permissive temperature, suggesting a genetic interaction between MAK2 and PKA signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together with our results, it is clear that, despite the similarities in cellular behaviors that accompany FG in diploids and haploids, and despite the fact that the same kinase pathways are involved, cell type-specific differences impose different regulatory dependencies and outcomes in the face of similar inputs. It will be interesting to compare the detailed regulatory arrangements in other yeasts and pathogenic fungi, whose filamentous behaviors generally require components orthologous to the MAPK and PKA signaling pathways (and the downstream transcription factors) first described in S. cerevisiae (Bruno et al 1996;Banuett 1998;Martinez-Espinoza et al 2004;Verstrepen and Klis 2006;Klosterman et al 2007;Rispail et al 2009;Hoi and Dumas 2010).…”
Section: Discussionmentioning
confidence: 99%